Peran Pemerintahan Di Kantor Wali Nagari Pinaga Aua Kuniang, Kabupaten Pasaman Barat - Raudhatul Natasya Annur; Ismi Rahmadhani; Piza Angelia Putri; Miftahul Jannah; Rizki Syafril (CV. ITTC INDONESIA, 2025)
Village governance still faces several challenges, including suboptimal public service delivery, difficulties in participatory policy formulation and implementation, and demands for transparent and accountable village financial management, particularly in villages that strongly adhere to Minangkabau customary values such as Nagari Pinaga Aua Kuniang, Pasaman Barat Regency. This study aims to describe and analyze the role of the village government at the Wali Nagari Office of Pinaga Aua Kuniang in the implementation of public services, policy formulation and implementation, village financial management, management of government apparatus, as well as the role of community institutions and the influence of customary values on village governance. This research employs a qualitative descriptive approach, with data collected through observation, interviews with village officials and community institutions, and documentation study. Data were analyzed qualitatively through data reduction, data display, and conclusion drawing. The findings indicate that the village government has performed its governmental functions relatively effectively, as reflected in administrative and social public services, participatory policy-making through village deliberation forums, and transparent and accountable financial management. Community institutions such as Bamus, LPM, PKK, Karang Taruna, and the Nagari Customary Council play an active role in supporting and supervising governance processes. Furthermore, Minangkabau customary values, particularly the principle of Adat Basandi Syarak, Syarak Basandi Kitabullah, serve as an important moral foundation in decision-making and problem-solving at the village level.